The Politics of Justification : Party Competition and Welfare-State Retrenchment in Denmark and the Netherlands from 1982 to 1998 - Green-Pedersen, Christoffer (Amsterdam University Press, 2002)
The Politics of Justification is an investigation of welfare retrenchment in Denmark and the Netherlands, 1982-1998. Welfare retrenchment is politically highly controversial, but still governments do retrench. This book argues that governments can implement retrenchment if they can achieve a party political consensus allowing them to frame retrenchment in a way that makes it seems justified to the electorate. In the Netherlands, such a consensus emerged in the mid 1980s due to the power of the CDA. It has allowed Dutch government to implement a number of welfare retrenchments. In Denmark, a consensus did not emerge until the Social Democratic Party re-entered government in 1993 explaining why the Danish welfare state has seen less retrenchment than the Dutch one. With its focus on the strategies of the political parties, the book differs from many other studies of the subject focusing on the role of political institutions.
The Politics of Justification onderzoekt de bezuinigingen op de sociale zekerheid die plaatsvonden in Nederland en Denemarken in de periode 1982-1998. Het korten op sociale voorzieningen ligt politiek uiterst gevoelig, maar toch snijden regeringen in hun uitgaven. Green-Pedersen bepleit dat regeringen bezuinigingen mogen doorvoeren als ze een partijpolitieke consensus bereiken die het mogelijk maakt de uitgavevermindering zó te formuleren dat het aanvaardbaar is voor het electoraat. In Nederland deed die situatie zich halverwege de jaren '80 voor door de macht van het CDA. In Denemarken daarentegen ontstond een dergelijke consensus pas in 1993 toen de Sociaal-Democratische Partij (SP) zijn herintrede deed in de regering. Dat verklaart waarom de Deense verzorgingsstaat minder bezuinigingen heeft gekend dan de Nederlandse.
English
Keywords: Politics & government; political science; politicologie